Facebook's power to mobilize fans in the electoral campaign. Case Study: 2019 European Parliamentary Elections in Romania - Tasente, Tanase (Technium Social Sciences Journal, 2021)
Since 2008, when Barack Obama won the United States election thanks to Facebook, that success model has been improved year by year, and at present Social Media has become the main channel of communication in electoral campaigns, ahead of traditional media (TV, radio, newspapers). The novelty of this communication mechanism can be described by decentralizing the communication to social groups of online opinion leaders and eliminating the horizontal dimension, in which mass-media and political actors played fundamental roles in disseminating the political message to the public. In Social Media, the message is decentralized from source (political actor's Facebook page) by some ordinary users, which in time become influential leaders in the virtual environment. Moreover, political parties that managed to mobilize most fans to disseminate political information in their social groups (strong and weak links) managed to achieve better electoral scores. Our study focused on analyzing the campaign on Facebook in the electoral campaign of the main three parties in Romania, which won the most mandates in the European Parliament: the National Liberal Party (yellow), the Social Democratic Party (red) and the Union "Save Romania" (blue). The election campaign took place from 27 April 2019 to 25 May 2019 and the voting day was on 26 May 2019.